Juridical Analysis of The Fairness Aspects of the Implementation of the Ar’s Length Principle to Domestic Related-party Transactions in Indonesia - Muhammad Hanif Arkanie; Amin Purnawan (Universitas Islam Sultan Agung, 2026)
This article examines the fairness and legal certainty of applying the Arm’s Length Principle (ALP) to domestic affiliated transactions in Indonesia. Although the ALP was originally designed to prevent tax avoidance through profit shifting across jurisdictions with different tax rates, Indonesian tax law also applies it to domestic related-party transactions in which the parties are generally subject to the same tax rate. Using normative legal research, this study employs statutory, conceptual, and case approaches to analyze relevant tax regulations and selected Tax Court decisions. The findings indicate that the domestic application of the ALP raises significant fairness concerns because primary adjustments are not always accompanied by effective corresponding adjustments, thereby creating a risk of economic double taxation. Legal certainty is further weakened by inconsistent judicial reasoning and procedural limitations in the current regulatory framework. This article argues that a more proportionate policy model is required, including stronger protection of taxpayers’ rights to corresponding adjustments, clearer limits on primary adjustments in domestic cases, and broader use of Advance Pricing Agreements as a preventive mechanism. These reforms are necessary to align domestic transfer pricing regulation with the principles of fairness, proportionality, and legal certainty.